2016
DOI: 10.1103/physrevapplied.6.064014
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Magnetometer Multisensor Array for rf Interference Mitigation and Unshielded Detection of Nuclear Quadrupole Resonance

Abstract: An array of four 87 Rb vector magnetometers are used to detect nuclear quadrupole resonance (NQR) signals in an unshielded environment at 1 MHz. With a baseline of 25 cm, the length of the array, radio-frequency interference mitigation (RFIM) is also demonstrated; a radio-station signal is suppressed by a factor of 20 without degradation to the signal of interest. With these compact sensors, in which the probe beam passes through twice, the fundamental limit to detection sensitivity is found to be photon shot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 55 publications
2
23
0
Order By: Relevance
“…The optimization adapts an IIR filter with a transfer function in the form of Eq. (7). The best noise rejection is obtained applying eight nonzero coefficients among the parameter set.…”
Section: Optimized Feedback Loop Designmentioning
confidence: 99%
“…The optimization adapts an IIR filter with a transfer function in the form of Eq. (7). The best noise rejection is obtained applying eight nonzero coefficients among the parameter set.…”
Section: Optimized Feedback Loop Designmentioning
confidence: 99%
“…Equation (4) shows that the first order differential value of the zero-field resonance signal has a maximum only when the magnetic field along the three directions becomes zero simultaneously. Therefore, we can compensate the triaxial magnetic field by maximizing the first order differential value of the zero-field resonance.…”
Section: B the Zero-field Resonance And Its Differentialmentioning
confidence: 99%
“…The atomic magnetometer operating in the spin-exchange relaxation-free (SERF) regime is currently known as the most sensitive detector in the low frequency magnetic field. The high sensitivity of SERF magnetometers has broadened the application range from fundamental physics research [1], [2] and magnetic property tests [3], [4] to portable devices for magnetoencephalography (MEG) [5], [6]. It is operated with a high density of alkali atoms in extremely weak…”
Section: Introductionmentioning
confidence: 99%
“…Because atoms have well-known properties and give reproducible measurements that can easily be related to SI units, they are ideal candidates for use in a new generation of sensors in the growing field of quantum technologies [20]. For example, atom-based sensors have been used for precise measurements of magnetic fields [21,22] and gravity [23,24] and are beginning to be marketed and used in fields as diverse as biomedical sensing [25], geomagnetic [26], and defense applications [27]. A subclass of atom-based sensors includes those based upon Rydberg atoms, atoms that have been excited to a high principal quantum number n. It has been shown that Rydberg atoms are excellent sensors for weak electromagnetic fields in the radio-frequency, microwave, and THz ranges [28][29][30][31], as well as for trace gas detection [32].…”
Section: Introductionmentioning
confidence: 99%